factorize
xsquared-x-6.
how do u do this?
well you can use, the following formula to find theroots of the quadratic equation:
X1 = 0.5*(1 + sqrt(1 + 24)) = 3
X2 = 0.5*(1 - sqrt(1 + 24)) = -2
thus the factorization is: (x-3)*(x+2)
the general fomula for finding the roots of a quadratic equation of the following form:
p(x) = a*x^2 + b*x + c
is:
X1 = (-b + sqrt(b^2 - 4*a*c)) / (2*a)
X2 = (-b - sqrt(b^2 - 4*a*c)) / (2*a)
also notice that if "a" does not equal 1 the factorization will be
a*(x-X1)*(x-X2)